Application of educational games as an Arabic language learning method at MTs Negeri 2 Deli Serdang - Septiana, Eka; Salsabila, Anggun; Salsabila, Annisa; Hasugian, Yana Kianshi (Holistic Science, 2024)
Arabic language learning is often carried out by Islamic educational institutions such as madrasa-based or integrated Islamic schools. Nowadays, Arabic is often considered a scary and difficult subject to understand. Method is a method or path that must be followed in achieving learning goals, including Arabic language lessons. By holding educational games as a learning method, it can support students' learning process. This can happen because students will feel happy when learning. The method used by the author in this article is a qualitative descriptive method, where data is collected through interviews and observations at MTs Negeri 2 Deli Serdang, North Sumatra. The educational games applied to learning Arabic in this school include crossword puzzles, snakes and ladders, and the singing method for memorizing vocabulary.